Pengaruh Pengawasan Atasan Langsung Terhadap Kinerja Pegawai Sekretariat DPRD Kota Padang - Rossa Ananda Zuliana; Lusi Susanti; Ahmad Sabandi; Widiawati, Widiawati (CV. ITTC INDONESIA, 2026)
Employee performance is the result of employee work in carrying out their duties and responsibilities which is measured through quality, quantity, timeliness, and effectiveness of their contribution in achieving the organization. Direct supervisor supervision is a control process carried out actively and continuously by superiors towards subordinates during the implementation of work, with the aim of ensuring conformity between task implementation and organizational plans. This study aims to see the effect of direct supervisor supervision (variable X) on employee performance variables (variable Y). The population in this study were 111 employees of the Secretariat of the Regional People's Representative Council of Padang City. The sample in this study amounted to 87 employees using the Cochran formula with a confidence level of 95%. The technique for determining samples in each stratum section was using the proportionate stratified random sampling technique. The results of this study indicate that there is a significant influence of direct supervisor supervision on the performance of employees of the Secretariat of the Regional People's Representative Council of Padang City. With a significance value of 0.000 <0.05 and a regression coefficient value of 0.593. So it can be concluded that there is a significant influence of the direct supervisor supervision variable (X) on the employee performance variable (Y).